Striking hematological abnormalities in patients with microcephalic osteodysplastic primordial dwarfism type II (MOPD II): A potential role of pericentrin in hematopoiesis. Issue 2 (17th September 2013) - Unal, Sule; Alanay, Yasemin; Cetin, Mualla; Boduroglu, Koray; Utine, Eda; Cormier‐Daire, Valerie; Huber, Celine; Ozsurekci, Yasemin; Kilic, Esra; Simsek Kiper, Ozlem Pelin; Gumruk, Fatma
Abstract Background Microcephalic osteodysplastic primordial dwarfism type II (MOPD II) is a rare primordial dwarfism that is similar to Seckel syndrome. Seckel syndrome is known to be associated with various hematological abnormalities; however, hematological findings in MOPD II patients have not been previously reported. The present study aimed to describe the hematological findings in a series of eight patients with MOPD II from a single center. Materials and Methods The study included eight patients with MOPD II that were analyzed via molecular testing, and physical and laboratory examinations. Results Molecular testing showed that seven of the eight patients had pericentrin (PCNT) gene mutations. Hematological evaluation showed that 7 (87.5%) patients had thrombocytosis, 6 (75%) had leukocytosis, 5 (62.5%) had both leukocytosis and thrombocytosis, and 2 (25%) had anemia. Conclusions We report leukocytosis and thrombocytosis as a common hematologic abnormality in patients with MOPD II. The present findings may improve our understanding of the potential function of the PCNT gene in hematopoietic cell proliferation and differentiation. Pediatr Blood Cancer 2014;61:302–305. © 2013 Wiley Periodicals, Inc.